Evaluation of Transparency and PH of Ernestina Power Plant Watershed – Rio Grande do Sul - Palma, João Victor Nolasco; Pereira Filho, Waterloo; Kramer, Gisieli; Kaiser, Eduardo Andre (Ciência e Natura, 2017)
The anthropic activities, such as the usage of land for agriculture, have been modifying the natural processes, mainly on aquatic environments. Following this statement, this work aimed at characterizing and analyzing the transparency and pH of the Ernestina power plant watershed (UHE) located on the state of Rio Grande do Sul, Brazil. The methodology consisted on the collection of water samples in six points of the watershed and laboratorial analysis of the limnological variables pH and Transparency. The results of the sample points show high values for transparency and basic pH levels associated to the absence of rainfall on the day before the field study. The analysis of the compiled results compared to previous researches shows that a seasonal eutrophication process that may be related to the inadequate usage of land on the microbasins that constitute the watershed in the face of intense rainfall.